Relationships of socioeconomic level with eating behavior of traditional food among adolescents. - Muhammad, Nur Hafizah; Abdul Karim, Muhammad Shahrim; Othman, Mohhidin; Ghazali, Hazrina (Mediterranean Center of Social and Educational Research, 2013)
Traditional food is never just about eating and fulfilling our biological needs; nevertheless it preserves the culture and tradition properties of a nation. Traditional food is known as representation of identity and embraces the components of cultural and heritage of a particular group of people in particular region. Malaysia has created distinctively traditional food based on the multi-ethnicity roots that lives together throughout the years such as Malay, Chinese and Indian communities. Presently, in this new and modern environment with economic prosperity of the country, young generation seems unappreciated the traditional food. They had been showered with Western fast food and other foreign foods, whereby traditional food is not their only option. Previous studies found socioeconomic level effects the eating behavior of traditional food, especially in adolescents. Therefore, this study aims to investigate the impact of socioeconomic level on adolescents’ eating behavior of traditional food in Malaysia situation by implementing Theory of Planned Behavior (TPB) as a background theory. Self-administered questionnaire was distributed to 655 secondary school students by using cluster sampling technique. Multiple linear regression (MLR) results indicated adolescents belong to lower (B = 0.28) and middle (B = 0.46) socioeconomic level family have the capability to control their intention to eat traditional food; whereas adolescents came from high socioeconomic level proved to rely on their attitudes towards traditional food (B = 0.34) to drive the intention to eat traditional food.